2005
DOI: 10.1016/j.infsof.2004.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A framework for evaluating a software bidding model

Abstract: This paper discusses the issues involved in evaluating a software bidding model. We found it difficult to assess the appropriateness of any model evaluation activities without a baseline or standard against which to assess them. This paper describes our attempt to construct such a baseline. We reviewed evaluation criteria used to assess cost models and an evaluation framework that was intended to assess the quality of requirements models. We developed an extended evaluation framework and an associated evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 9 publications
0
50
0
Order By: Relevance
“…Furthermore, once those models have been created, they need to be validated against the real world they are modeling. Kitchenham et al [28] propose a framework for validating bidding systems, which can also be used for evaluating SD or BN models. The evaluation framework is composed of five quality aspects: 1) syntactic quality, 2) semantic quality, 3) pragmatic quality, 4) test quality, and 5) value quality.…”
Section: Analysis Of the Results And Discussionmentioning
confidence: 99%
“…Furthermore, once those models have been created, they need to be validated against the real world they are modeling. Kitchenham et al [28] propose a framework for validating bidding systems, which can also be used for evaluating SD or BN models. The evaluation framework is composed of five quality aspects: 1) syntactic quality, 2) semantic quality, 3) pragmatic quality, 4) test quality, and 5) value quality.…”
Section: Analysis Of the Results And Discussionmentioning
confidence: 99%
“…It consists of evaluating five different qualities: Semantic, Syntactic, Pragmatic, Test and Value (see [3]). The framework is an extension of Lindland et al's framework for evaluating the quality of conceptual models [6].…”
Section: The Evaluation Frameworkmentioning
confidence: 99%
“…In a previous paper [3], we proposed a framework for evaluating a software bidding model, and suggested that such a framework might be useful for any expert-opinionbased model of a software process where there was little or no data available for model validation. In this paper, we present the results of two trials aimed at evaluating the framework.…”
Section: Introductionmentioning
confidence: 99%
“…There is some literature on software project bidding and its risk management now [4][5][6][7][8]. Kitchenham et al present a software project bidding framework that allows users to visualize the risk involved in an offer and to make appropriate bid/no bid decisions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Jørgensen and Carelius consider that risk premium overcompensated for the level of uncertainty leads to a higher price in software project bidding [6]. Kitchenham et al develop an extended evaluation framework and an associated evaluation process to evaluate software bidding model [7], and report two trials of the evaluation framework in software project bidding [8]. However, the investigations are usually limited in a certain segment or stage, for example cost and offer.…”
Section: Introductionmentioning
confidence: 99%